R-locus for roaned coat is associated with a tandem duplication in an intronic region of USH2A in dogs and also contributes to Dalmatian spotting. - Takeshi Kawakami; Meghan K Jensen; Andrea Slavney; Petra E Deane; Ausra Milano; Vandana Raghavan; Brett Ford; Erin T Chu; Aaron J Sams; Adam R Boyko (PLoS ONE, 2021)
Structural variations (SVs) represent a large fraction of all genetic diversity, but how this genetic diversity is translated into phenotypic and organismal diversity is unclear. Explosive diversification of dog coat color and patterns after domestication can provide a unique opportunity to explore this question; however, the major obstacle is to efficiently collect a sufficient number of individuals with known phenotypes and genotypes of hundreds of thousands of markers. Using customer-provided information about coat color and patterns of dogs tested on a commercial canine genotyping platform, we identified a genomic region on chromosome 38 that is strongly associated with a mottled coat pattern (roaning) by genome-wide association study. We identified a putative causal variant in this region, an 11-kb tandem duplication (11,131,835-11,143,237) characterized by sequence read coverage and discordant reads of whole-genome sequence data, microarray probe intensity data, and a duplication-specific PCR assay. The tandem duplication is in an intronic region of usherin gene (USH2A), which was perfectly associated with roaning but absent in non-roaned dogs. We detected strong selection signals in this region characterized by reduced nucleotide diversity (π), increased runs of homozygosity, and extended haplotype homozygosity in Wirehaired Pointing Griffons and Australian Cattle Dogs (typically roaned breeds), as well as elevated genetic difference (FST) between Wirehaired Pointing Griffon (roaned) and Labrador Retriever (non-roaned). Surprisingly, all Dalmatians (N = 262) carried the duplication embedded in identical or similar haplotypes with roaned dogs, indicating this region as a shared target of selection during the breed's formation. We propose that the Dalmatian's unique spots were a derived coat pattern by establishing a novel epistatic interaction between roaning "R-locus" on chromosome 38 and an uncharacterized modifier locus. These results highlight the utility of consumer-oriented genotype and phenotype data in the discovery of genomic regions contributing to phenotypic diversity in dogs.